Internal Audit and Leadership: How to Improve Productivity Service on The Islamic Rural Bank have to Use Capital - Tulus Suryanto; Effendi Effendi; Apun Syaripudi (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This study investigates whether the Internal Audit and Leadership significant effect to the productivity of banking services on islamic rural bank Bandar Lampung in partially and simultaneously. The approach used in this study is a qualitative and quantitative analysis. The incoming data is analyzed and tested by multiple linear regression. Before being tested by multiple linear regression, first tested by using validity and reliability test, to measure and test the questionnaire given to respondents, is quite valid and reliable. Leadership significant effect on productivity services in Islamic Rural Banks, by 19.3%. Internal Audit significant effect on productivity services at the Islamic Rural Bank, by 59.6%. Simultaneously testing indicate that the Leadership and Internal Audit jointly significant effect on productivity services in the Sharia Rural Banksby 78.9%. As for the remaining 21.1% influenced by other factors. This study contributes when leadership and internal audit plays together will be able to increase the productivity services inIslamic rural bank significantly. The results of this study can be used by management in improving the quality of human resources in Islamic rural bank. Needed good leadership: making quick decisions, always motivate employees or subordinates, always creative and innovate, communicate with employees or subordinates, a clear division of authority.